A Global and Sector-Based Comparison of OCT Angiography and Visual Field Defects in Glaucoma - Alan W. Kong; Marcus L. Turner; Murtaza Saifee; Mohit Jethi; Marta Mora; Yvonne Ou (Journal of Ophthalmology)
Purpose. To evaluate the correlation of optical coherence tomography angiography (OCTA) and spectral-domain optical coherence tomography (SD-OCT) with visual field for global and sector-based indices among glaucoma and glaucoma-suspected eyes. Patients and Methods. This is a retrospective study, and in total, 48 glaucoma eyes and 31 glaucoma suspect eyes were included. The correlation between visual field parameters and radial peripapillary capillary (RPC) vessel density via OCTA was compared to the correlation with retinal nerve fiber layer (RNFL) thickness via SD-OCT. The RPC vessel density and RNFL thickness were divided into eight sectors, which included the temporal upper, temporal lower, superotemporal, inferotemporal, superonasal, inferonasal, nasal upper, and nasal lower sectors. Pearson correlations with 95% confidence intervals were calculated with resampling, and correlations were compared with a Fisher Z transformation. Results. Both RPC vessel density (R = 0.63, 95% CI [0.24, 0.86]) and RNFL thickness (R = 0.49, 95% CI [0.23, 0.69]) were correlated with the mean deviation when comparing global indices of glaucoma patients. In glaucoma suspects, the correlations between the mean deviation and RPC vessel density (R = 0.21, 95% CI [−0.05, 0.49]) and RNFL thickness (R = 0.01, 95% CI [−0.35, 0.39]) were not significant. Glaucoma eyes had the highest correlation between the mean sensitivity and RPC vessel density and RNFL thickness for the superotemporal, superonasal, temporal upper, and inferotemporal sectors. Conclusion. Across a diverse population and heterogeneous glaucoma types, RPC vessel density measurements correlate with global and sector-wise visual field indices similar to RNFL thickness.